2023
DOI: 10.5829/ije.2023.36.01a.07
|View full text |Cite
|
Sign up to set email alerts
|

Study on the Application of Sustainable Construction in the Development of the Likupang Special Economic Zone

Abstract: Sustainability construction is starting to become a focus in developing countries such as Indonesia. There are many problems that must be considered in the implementation of sustainable construction. The purpose of this study is to analyze the factors that influence the implementation of sustainable construction in the Likupang SEZ project. The method used is a mixed-method to determine various factors that affect sustainable construction. This research involves various stakeholders such as contractors, consul… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 17 publications
0
1
0
Order By: Relevance
“…Other than that, human resources have a positive impact on sustainability after applying good government and defense culture factors. Several studies concluded that factors and variables must be directly related to sustainable building, which applies economic, environmentally friendly, comprehensive management, and social culture [6,[8][9][10]. Environmental sustainability has been implemented in several countries to solve those problems.…”
Section: Introductionmentioning
confidence: 99%
“…Other than that, human resources have a positive impact on sustainability after applying good government and defense culture factors. Several studies concluded that factors and variables must be directly related to sustainable building, which applies economic, environmentally friendly, comprehensive management, and social culture [6,[8][9][10]. Environmental sustainability has been implemented in several countries to solve those problems.…”
Section: Introductionmentioning
confidence: 99%